Crimes Burglary on Banks in Jordan and Stand of Social Media Sites Users from them - Al-faouri, Fathi; Aseel Al Shawareb, Hesham Alomyan, Qasem Althubetat,; Ibrahim Yousef, Ali Aldabbas, (Opción)
This analytical study came to uncover causes of a disturbing phenomenon to the Jordan Community in general and the security corps in particular. In the year 2018, the phenomenon of armed burglary on the foundations, specifically banks. Aware of analyses commentaries and inquiries on social media accompanied this phenomenon, and expressed the stand of users of these means towards crimes of burglary. This study also tackled the causes of these crimes from the point of view of perpetrators and users of social media sites, that is through informing their view by analyzing commentaries published about these crimes on the Facebook specifically. Results had shown the connection of this phenomenon with poverty and unemployment in Jordan as the most important causes of committing this crime. But what is related with sites of social media, that was the most abundant stand reflected by users of social media sites. It is disbelieving those incidents and considering them representations or plays. They also showed an implied and non-frank sympathy with perpetrators of these crimes through justification of committing these crimes, because of poverty and through proposition of lightening punishments. The study submitted a group of recommendations connected with their results.